From Crime Control Model to Due Process Model: A Critical Study of Wiretapping Arrangement by the Corruption Eradication Commission of Indonesia - Hwian Christianto (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2020)
This study compares three formal criminal laws on the corruption act to show the importance of due process model for wiretapping/lawful interception in Indonesia. Investigators of Indonesian Corruption Eradication Commission (KPK) assume that the implementation of wiretapping based on the due process model decelerate the performance and independence of corruption eradication. The problem particularly happens on the execution of caught in the act operation. This study covers the design of wiretapping on corruption case linked with the due process model as an effort to guarantee the right of privacy. Firstly, legislators accentuated an effective corruption eradication, which highlights the implementation of the crime control model. Secondly, the latest amendment to the Law on Corruption Eradication Commission of Indonesia alters wiretapping to become a procedural activity for stronger synergy among the law enforcement institutions. The regulation of wiretapping as a method to reveal corruption case in Indonesia does not adhere to the due process model entirely. The wiretapping still tends to deal with stages of preliminary-investigation, investigation, prosecution, and the execution of internal approval process. From Crime Control Model to Due Process Model: Studi Kritis Pengaturan Penyadapan oleh Komisi Tindak Pidana Korupsi Republik Indonesia AbstrakHasil penelitian atas tiga undang-undang hukum pidana formil terkait tindak pidana korupsi di Indonesia menunjukkan pentingnya model due process dalam penyadapan. Penyidik Komisi Pemberantasan Korupsi Republik Indonesia memandang pelaksanaan penyadapan berdasarkan model due process memperlambat kinerja dan independensi penegakan korupsi terutama dilakukannya Operasi Tangkap Tangan. Artikel ini membahas rancang bangun penyadapan pada tindak pidana korupsi dikaitkan dengan model due process sebagai upaya menjamin hak asasi manusia, secara khusus hak privasi. Pertama, awalnya pembentuk undang-undang lebih menekankan pemberantasan tindak pidana korupsi secara efektif sehingga menunjukkan penerapan model pengawasan tindak pidana.  Kedua, UU KPK RI  mengubah penyadapan lebih prosedural dengan harapan menguatkan sinergitas antar lembaga penegak hukum. Pengaturan penyadapan atas tindak pidana korupsi di Indonesia masih belum sepenuhnya memberlakukan model due process. Penyadapan masih bersifat sektoral dengan mencakup tahap penyelidikan, penyidikan dan penuntutan serta menjalankan proses perijinan secara internal. Kata kunci: korupsi, model due process, model pengawasan tindak pidana.DOI: https://doi.org/10.22304/pjih.v7n3.a7